1992
DOI: 10.1097/00006123-199207000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Expansion of Hypertensive Intracerebral Hemorrhage

Abstract: We report a series of 10 patients who had a rapid expansion of a hypertensive intracerebral hemorrhage (HICH). It occurred in approximately 3% of 320 patients who sought treatment for HICH during the past 2 years. The site of hemorrhage was the putamen in 6 patients and the thalamus in 4 patients. Neurological deterioration occurred in a mean time of 40 hours after the onset of symptoms (range, 5.5-109 h). Fifty percent of all patients deteriorated within 24 hours. Persistent hypertension was recorded in all p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Although a few methods are available for treatment of spontaneous cerebral hemorrhage, the treatment is generally classified according to 2 major groups: hematoma evacuation by craniotomy or drainage by burrhole. 1) …”
Section: Discussionmentioning
confidence: 99%
“…Although a few methods are available for treatment of spontaneous cerebral hemorrhage, the treatment is generally classified according to 2 major groups: hematoma evacuation by craniotomy or drainage by burrhole. 1) …”
Section: Discussionmentioning
confidence: 99%
“…Even though high BP is a treatable condition, there is an unfortunate dearth of studies that have investigated the relevance of high BP to HE. Some previous reports [13–15] involving relatively small number of patients indicated that HE was associated with persistent hypertension. However, a prospective study [3] that included 103 patients with ICH within the first 3 h after the onset of symptoms, failed to find evidence that BP was associated with HE.…”
Section: Discussionmentioning
confidence: 99%
“…If high BP is a factor involved in the pathogenesis of HE, this would have important therapeutic implications. Small studies reported years ago and some retrospective studies more recently have reported that haematomas expand in patients with uncontrolled high BP [12–17]. However, there is no clear evidence of this association from prospective observational studies [3,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The rapid expansion of a sICH has been frequently reported 1)14). However, we found limited reports describing the rapid spontaneous decrease in the volume of the hematoma observed in ICH 4).…”
Section: Discussionmentioning
confidence: 95%